COMMUNICATION BARRIER TOWARDS ORPHANAGE STUDENT LEARNING PROCESS DURING COVID-19 PANDEMIC - Dewi Anggrayni; Nur Choiro Siregar; Mohammad Zamroni; Rosmawati Binti Mohamad Rasit (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Validity and reliability are the most important aspects to determine the quality of research conducted by researchers. This study aims to measure the validity and reliability of the communication barrier instrument in the learning process of orphanages during the pandemic. The instruments used in this study were 20 items. This research design applies a quantitative paradigm. The validity and reliability of the communication barrier instrument were measured by Rasch Model Analysis (RMA) using Winsteps version 3.71.0.1 software. The students involved in this study consisted of 380 students from orphanages in the city and district of Bogor. RMA analyzed six aspects in determining the instrument's stability: person and item reliability, item difficulty level, item polarity, misfit item, unidimensional, and person map item. Based on these seven aspects, the instrument used in this study was valid and reliable to measure students' communication barriers during the pandemic. The importance of valid and reliable instruments can be helpful to determine the condition of students during the learning process during the pandemic. The instruments are essential for parents and teachers to deal with student changes during the learning process. Public educators can use the implications of this research and interested people to measure the communication barrier condition of students of the process during the pandemic. Future studies are needed to conduct testing for all students, from elementary to higher education institutions with more comprehensive research sites.